Discovery of antibacterial agents targeting biofilm formation: total synthesis and in vitro investigation of amycolasporins. Issue 34 (15th August 2022) - Wu, Wenxi; Mu, Yu; Tan, Junfeng; Wang, Zixuan; Zhang, Chen; Li, Guiding; Jin, Ying; Huang, Xueshi; Han, Li
Abstract : The total synthesis of antibacterial amycolasporin A, (±) amycolasporins B and C and their analogues (18, 19, 30a and 30d–30f ) was introduced; 30d obviously inhibited bacterial biofilm formation and promoted intracellular ROS release. Abstract : Three monoterpene alkaloids amycolasporin A and (±) amycolasporins B and C have been synthesized for the first time from commercially available materials in yields of 31%, 14% and 21%, respectively. Their six analogues (18, 19, 30a and 30d–30f ) were synthesized through a similar protocol. Meanwhile, the antibacterial activity of all synthesized molecules was evaluated, showing different levels of bioactivity. Among them, analogue 30d was screened as the most effective antibacterial candidate against E. coli (MIC value, 12.5 μg mL −1 ) and S . aureus (MIC value, 12.5 μg mL −1 ). Further investigation showed that 30d obviously inhibited biofilm formation and disrupted the preformed biofilm of E . coli and S . aureus by promoting intracellular ROS release.